Securing systems applied security architecture and threat models - Schoenfield, Brook S. E. (CRC Press, 2015)
Internet attack on computer systems is pervasive. It can take from less than a minute to as much as eight hours for an unprotected machine connected to the Internet to be completely compromised. It is the information security architect's job to prevent attacks by securing computer systems. This book describes both the process and the practice of assessing a computer system's existing information security posture. Detailing the time-tested practices of experienced security architects, it explains how to deliver the right security at the right time in the implementation lifecycle.Securing System